A Broken P1-Nonconforming Finite Element Method for Incompressible Miscible Displacement Problem in Porous Media. (11th December 2013) - Chen, Fengxin; Chen, Huanzhen
Abstract : An approximate scheme is defined for incompressible miscible displacement in porous media. This scheme is constructed by using immersed interface finite element method for the pressure equation which is based on the broken P 1 -nonconforming piecewise linear polynomials on interface triangular elements and utilizing finite element method for the concentration equation. Error estimates for pressure in broken H 1 norm and for concentration in L 2 norm are presented.